Pengaruh disiplin kerja dan gaya kepemimpinan kerja terhadap kinerja karyawan d'Arcici hotel plumpang jakarta utara: The influence of work discipline and leadership style on employee performance at d'Arcici Hotel Plumpang, North Jakarta - Yohana Elizabeth; Mohammad Amas Lahat; Dani Chandra Utama (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study aims to analyze the effect of work discipline (X1) and the Work Leadership Style (X2) on employee performance (Y) at D'Arcici Hotel Plumpang, North Jakarta, using a quantitative approach and descriptive design. As many as 61 employees were used as samples through saturated sampling techniques, and data were collected using questionnaires, observations, interviews, documentation, and literature studies. Data was analyzed through the Validity Test (Pearson Product Moment) and Reliability (Cronbach's Alpha), followed by the classic assumption test (normality of the Kolmogorov-Smirnov and Normal Probability Plot, Multicolinearity of Tolerance and VIF, and heteroscedasticity of spearman’s RHO). The hypothesis is tested using multiple linear regression analysis, T test (partial), F test (simultaneous), and the coefficient of determination (R²). The results show that work discipline has a positive and significant significant effect on employee performance, while the work leadership style has a positive but not significant significant. However, simultaneously, both of these variables have a positive and significant influence on employee performance, with the coefficient of determination (R²) of 0.661, which means 66.1% of employee performance variations are explained by work discipline and work leadership style, while the remaining 33.9%influenced by other factors outside of this study.